Human RIPK3 C-lobe phosphorylation is essential for necroptotic signaling - Yanxiang Meng; Christopher R. Horne; Andre L. Samson; Laura F. Dagley; Samuel N. Young; Jarrod J. Sandow; Peter E. Czabotar; James M. Murphy (Cell Death and Disease, 2022)
Abstract Necroptosis is a caspase-independent, pro-inflammatory mode of programmed cell death which relies on the activation of the terminal effector, MLKL, by the upstream protein kinase RIPK3. To mediate necroptosis, RIPK3 must stably interact with, and phosphorylate the pseudokinase domain of MLKL, although the precise molecular cues that provoke RIPK3 necroptotic signaling are incompletely understood. The recent finding that RIPK3 S227 phosphorylation and the occurrence of a stable RIPK3:MLKL complex in human cells prior to exposure to a necroptosis stimulus raises the possibility that additional, as-yet-unidentified phosphorylation events activate RIPK3 upon initiation of necroptosis signaling. Here, we sought to identify phosphorylation sites of RIPK3 and dissect their regulatory functions. Phosphoproteomics identified 21 phosphorylation sites in HT29 cells overexpressing human RIPK3. By comparing cells expressing wild-type and kinase-inactive D142N RIPK3, autophosphorylation sites and substrates of other cellular kinases were distinguished. Of these 21 phosphosites, mutational analyses identified only pT224 and pS227 as crucial, synergistic sites for stable interaction with MLKL to promote necroptosis, while the recently reported activation loop phosphorylation at S164/T165 negatively regulate the kinase activity of RIPK3. Despite being able to phosphorylate MLKL to a similar or higher extent than wild-type RIPK3, mutation of T224, S227, or the RHIM in RIPK3 attenuated necroptosis. This finding highlights the stable recruitment of human MLKL by RIPK3 to the necrosome as an essential checkpoint in necroptosis signaling, which is independent from and precedes the phosphorylation of MLKL.